Strategies for Enhancing Services Based on Information Systems and Global Marketing Research at PT Angkasa Pura Indonesia Airports - Mahardhika Pasha; Aden Muhamad Faisal; Dicky Kurniawan; Juliater Simarmata (Jurnal Ilmu Multidisiplin, 2025)
This articles “Strategies for Enhancing Services Based on Information Systems and Global Marketing Research at PT Angkasa Pura Indonesia Airports” explores the role of information systems and global marketing research in enhancing airport service quality at PT Angkasa Pura Indonesia. Persistent challenges such as prolonged waiting times, poorly managed queues, and insufficient facilities for special needs passengers have impacted passenger satisfaction and the airport's reputation. Leveraging big data and Know Your Customer (KYC) systems presents an opportunity to address these issues.Using a qualitative case study approach, data were collected through in-depth interviews, observations, and document analysis. SWOT analysis was applied to evaluate internal strengths, weaknesses, external opportunities, and threats. The findings reveal that KYC implementation effectively utilizes big data for service personalization and operational efficiency. The Internal Factor Evaluation (IFE) score of 2.89 and the External Factor Evaluation (EFE) score of 2.95 highlight strong internal and external factors. However, challenges remain, including infrastructure limitations and low customer awareness of the KYC system.The recommended strategy is to maximize strengths to address threats (ST strategy). Key steps include improving customer education on KYC, enhancing accessibility at remote airports, and automating customer service processes. These efforts aim to improve passenger satisfaction, strengthen competitiveness, and elevate the airport's global standing.